Novel Mechanism for Buffering Dietary Salt in Humans: Effects of Salt Loading on Skin Sodium, Vascular Endothelial Growth Factor C, and Blood Pressure - Selvarajah, Viknesh; Mäki-Petäjä, Kaisa M.; Pedro, Liliana; Bruggraber, Sylvaine F.A.; Burling, Keith; Goodhart, Anna K.; Brown, Morris J.; McEniery, Carmel M.; Wilkinson, Ian B. (Hypertension (Dallas, Tex. 1979), 2017)
High dietary sodium intake triggers increased blood pressure (BP). Animal studies show that dietary salt loading results in dermal Na + accumulation and lymphangiogenesis mediated by VEGF-C (vascular endothelial growth factor C), both attenuating the rise in BP. Our objective was to determine whether these mechanisms function in humans. We assessed skin electrolytes, BP, and plasma VEGF-C in 48 healthy participants randomized to placebo (70 mmol sodium/d) and slow sodium (200 mmol/d) for 7 days. Skin Na + and K + concentrations were measured in mg/g of wet tissue and expressed as the ratio Na + :K + to correct for variability in sample hydration. Skin Na + :K + increased between placebo and slow sodium phases (2.91±0.08 versus 3.12±0.09; P =0.01). In post hoc analysis, there was a suggestion of a sex-specific effect, with a significant increase in skin Na + :K + in men (2.59±0.09 versus 2.88±0.12; P =0.008) but not women (3.23±0.10 versus 3.36±0.12; P =0.31). Women showed a significant increase in 24-hour mean BP with salt loading (93±1 versus 91±1 mm Hg; P <0.001) while men did not (96±2 versus 96±2 mm Hg; P =0.91). Skin Na + :K + correlated with BP, stroke volume, and peripheral vascular resistance in men but not in women. No change was noted in plasma VEGF-C. These findings suggest that the skin may buffer dietary Na + , reducing the hemodynamic consequences of increased salt, and this may be influenced by sex.